Impact of Neurodevelopmental Disorders on Bowel Management Outcomes in Children with Functional Constipation. Issue 3 (9th August 2022) - Seidler, Gabriella R.; Knaus, Maria E.; Beyene, Tariku J.; Ahmad, Hira; Lu, Peter L.; Gasior, Alessandra C.; Halaweish, Ihab; Wood, Richard J.
Abstract : Objectives: Patients experiencing functional constipation (FC) can participate in structured bowel management programs (BMPs) to manage constipation or fecal incontinence when standard management fails. We sought to evaluate the efficacy of BMPs for children with FC with and without neurodevelopmental disorders. Methods: We performed a retrospective review of children with FC who participated in our BMP from 2014 to 2021. Stool/urinary continence, bowel regimen, surgical history, parent-reported outcomes measures (PROMs: Cleveland Clinic Constipation Score, Baylor Continence Scale, Vancouver Symptom Score for Dysfunctional Elimination), and Pediatric Quality of Life Inventory (PedsQL) were assessed pre- and at least 9 months post-BMP. Results: The cohort included 156 patients with a median age of 9 years and follow-up of 627 days (IQR: 389–808 days). Two sub-cohorts included patients with FC only (69%) and FC plus a neurodevelopmental disorder (31%): 59% attention-deficit/hyperactivity disorder, 33% autism spectrum disorder, and 8% obsessive-compulsive disorder. Both groups had significantly improved follow-up bowel movement frequency and continence (39%–90% neurodevelopmental, 44%–82% FC only, P < 0.001) and urinary continence (65%–90% neurodevelopmental, 69%–91% FC only, P < 0.02). There was a significant improvement in most of the PROMs at follow-up. Both groups experienced a clinically meaningful improvement in overall PedsQL scores (pre- and postBMP difference of >4.5). Conclusions: Patients with FC with and without a neurodevelopmental disorder had significant improvement in stool and urinary continence after undergoing a BMP. Further studies are needed to see if this improvement is durable over a longer period of time in this challenging cohort.